2020
DOI: 10.3847/1538-4357/ab908b
|View full text |Cite
|
Sign up to set email alerts
|

Solar Filaments and Interplanetary Magnetic Field Bz

Abstract: The direction of the axis of an interplanetary coronal mass ejection (ICME) plays an important role in determining if it will cause a geomagnetic disturbance in the Earth’s magnetosphere upon impact. Long period southward-pointing ICME fields are known to cause significant space weather impacts and thus geomagnetic storms. We present an extensive analysis of CME–ICME directionality using 86 halo-CMEs observed between 2007 and 2017 to compare the direction of the source filament axial magnetic field on the Sun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…A number of studies also successfully compared magnetic flux rope properties, such as the magnetic flux, the chirality, and its helicity sign determined from posteruptive arcades, flare ribbons, and coronal dimmings measured close to the Sun with magnetic cloud properties at 1 AU (Qiu et al 2007;Yurchyshyn 2008;Hu et al 2014;Marubashi et al 2015;Gopalswamy et al 2017b;Palmerio et al 2017Palmerio et al , 2018James et al 2017;Aparna and Martens 2020). The total amount of magnetic flux ejected during an eruption is estimated by the total reconnection flux in the wake of the CME or sometimes also by the magnetic flux involved in coronal dimming regions, which form the footprint of CMEs in the low corona (Mandrini et al 2005;Attrill et al 2006;Qiu et al 2007;Hu et al 2014).…”
Section: Coronal Sources Of Solar Eruptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies also successfully compared magnetic flux rope properties, such as the magnetic flux, the chirality, and its helicity sign determined from posteruptive arcades, flare ribbons, and coronal dimmings measured close to the Sun with magnetic cloud properties at 1 AU (Qiu et al 2007;Yurchyshyn 2008;Hu et al 2014;Marubashi et al 2015;Gopalswamy et al 2017b;Palmerio et al 2017Palmerio et al , 2018James et al 2017;Aparna and Martens 2020). The total amount of magnetic flux ejected during an eruption is estimated by the total reconnection flux in the wake of the CME or sometimes also by the magnetic flux involved in coronal dimming regions, which form the footprint of CMEs in the low corona (Mandrini et al 2005;Attrill et al 2006;Qiu et al 2007;Hu et al 2014).…”
Section: Coronal Sources Of Solar Eruptionsmentioning
confidence: 99%
“…CMEs erupting in the southern (northern) hemisphere tend to have a positive (negative) helicity sign (hemispheric helicity rule, e.g., Pevtsov et al 2003). Recently, Aparna and Martens (2020) investigated the directionality (chirality) of 86 CMEs-ICME pairs by comparing the orientation of their flux rope axes close to the Sun with the direction of the interplanetary magnetic field near Earth at L1. An agreement between the northward/ southward orientation of Bz between ICMEs and their CME source regions was found in 85% of the cases, which is comparable to earlier results by Palmerio et al (2018) and Yurchyshyn (2008), which found agreement for 55% and 77% of their cases.…”
Section: Coronal Sources Of Solar Eruptionsmentioning
confidence: 99%
“…Webb (2002) found a similarly strong association in his study of halo CMEs (his statistics also included corona dimmings). The orientation of the magnetic field in magnetic clouds and the Bz component of the leading polarity field in interplanetary CMEs (ICMEs) shows a strong correlation with the orientation of the magnetic field in the CME source regions/erupting filaments (e.g., Bothmer & Rust 1997;Marubashi 1997;Aparna & Martens 2020). Thus, routine observations of filaments, their topological properties (e.g., chirality), and Doppler velocity are critical for predicting the properties of CMEs and their potential geomagnetic impact for operational space weather forecast.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing these quantities can give substantial clues about predicting the devastating geomagnetic storms which ravage power supplies on Earth and satellites in space. Aparna & Martens (2020) analysed filaments in CME source locations and their IMF counterparts at Earth using the dataset of halo-CMEs from 2007-2017. With the largest data-set ever used for such a study, they observationally established that a trend prevails in the relation between the direction of axial field of a CME and that of the IMF near the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Yurchyshyn has given an agreement rate of 77% of cases. Aparna & Martens (2020), hereafter AM20, considers all the halo-CMEs between 2007 and 2017 and analyze their corresponding filaments on the Sun to get the axial field direction to compare with the Bz component of the IMF near the Earth. Their data-set is by far the largest and they classify ∼85% of the cases to have a match.…”
Section: Introductionmentioning
confidence: 99%